Village Level Community’s Engagement in Community-Based Water Supply Projects in Arumeru District, Arusha, Tanzania - Luvinga, Kepha Charles (Advances in Social Sciences Research Journal, 2025)
This study assessed village-level community engagement in Community-Based Water Supply Projects (CBWSPs) in Akheri Ward, Meru District Council, Arusha, Tanzania. A cross-sectional research design was employed, and simple random sampling was used to select 120 community members as respondents. Data were collected through questionnaires and analyzed descriptively using SPSS version 21.The findings reveal that community engagement in CBWSPs is primarily driven by sustainable water resource management (19.2%) and the need to increase access to clean and safe water (19.2%). Additionally, disaster resilience (16.7%) and compliance with regulations and policy frameworks (15.0%) are significant motivators. These factors highlight the community’s recognition of both the immediate and long-term benefits of water resource management. Furthermore, the study indicates that community participation in CBWSPs is considerable, with active involvement through village-level water user committees and the implementation of sustainable water supply initiatives. These structures enable local people to contribute to decision-making, ensure accountability, and promote resource sustainability. The study underscores the importance of strengthening institutional support, enhancing community awareness, and improving participatory governance to sustain engagement in CBWSPs.